Statistics of ionospheric scintillation occurrence over European high latitudes - Sreeja, V.; Aquino, Marcio (Elsevier, 2014)
Rapid fluctuation in the amplitude and phase of transionospheric radio signals caused by small scale ionospheric plasma density irregularities is known as scintillation. Over the high latitudes, irregularities causing scintillation are associated with large scale plasma structures and scintillation occurrence is mainly enhanced during geomagnetic storms. This paper presents a statistical analysis of scintillation occurrence on GPSL1C/A signal at a high latitude station located in Bronnoysund (geographic latitude 65.5°N, geographic longitude 12.2°E; corrected geomagnetic (CGM) latitude 62.77°N), Norway, during the periods around the peaks of solar cycles 23 (2002–2003) and 24 (2011–2013). The analysis revealed that the scintillation occurrence at Bronnoysund during both the solar maximum periods maximises close to the midnight magnetic local time (MLT) sector. A higher occurrence of scintillation is observed on geomagnetically active days during both the solar maximum periods. The seasonal pattern of scintillation occurrence indicated peaks during the summer and equinoctial months. A comparison with the interplanetary magnetic field (IMF) components By and Bz showed an association of scintillation occurrence with the southward IMF Bz conditions.